2016
DOI: 10.21292/2075-1230-2016-94-6-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Tuberculosis Development in Children With Latent Tuberculosus Infection

Abstract: Материалы и методы. Проведен анализ в динамике клинических, рентгенологических, иммунологических данных 127 детей -при по становке диагноза ЛТИ и через 12 мес. наблюдения. Также проведен комплекс иммунологических методов для оценки гуморального и клеточного иммунитета у пациентов с ЛТИ и больных туберкулезом.Результаты. Установлены высокая отрицательная прогностическая значимость наличия контакта с больным туберкулезом, сопутствующей патологии, отказа от проведения превентивной терапии, а также низкая эффектив… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Thus, the test specificity was 99.0-99.7% (20). The high effectiveness of the test in clinical practice has been confirmed by many authors (21)(22)(23). Studies have demonstrated that the use of the RTA test for TB screening has significantly increased the detection rate of tuberculosis in primary health care facilities (in schoolchildren 8-17 years of age, it is 37-fold higher than that with the use of the Mantoux test) (24).…”
Section: Discussionmentioning
confidence: 84%
“…Thus, the test specificity was 99.0-99.7% (20). The high effectiveness of the test in clinical practice has been confirmed by many authors (21)(22)(23). Studies have demonstrated that the use of the RTA test for TB screening has significantly increased the detection rate of tuberculosis in primary health care facilities (in schoolchildren 8-17 years of age, it is 37-fold higher than that with the use of the Mantoux test) (24).…”
Section: Discussionmentioning
confidence: 84%
“…В первом десятилетии XXI столетия в России произошли серьезные изменения в диагностике туберкулезной инфекции у взрослого и детского Оригинальные статьи Original Articles населения. Появились новые диагностические им мунологические тесты с высокой чувствительно стью и специфичностью, позволившие выявлять предболезнь (латентную туберкулезную инфек цию -ЛТИ) еще до развития локальной формы туберкулеза как у детей, так и у взрослых [5][6][7][8][9][10][11].…”
Section: Introductionunclassified